Head to Toe of Financial Analytics in Businesses and Hierarchical Interrelationships amongst Its Benefits through ISM Methodology - Jauhar, Jyotin; Aggarwal , Remica (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
Financial analytics by bringing together data from all systems gives a holistic view of the business and broader insights which further helps to predict and improve performance. This research work discusses various challenges faced while implementing and executing financial analytics for businesses. It further explores the hierarchical inter-relationships amongst them with the help of ISM methodology.